Comparative Physicochemical Properties of Honey from Apis cerana indica and Apis dorsata Across Different Floral Origins in Khandesh, North Maharashtra, India - Sawarkar, Arun Baburao (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The aim of this study was to compare the physicochemical properties of honey produced by Apis cerana indica and Apis dorsata from three sites with distinct floral orgins (agriculture, forest, and urban) in Khandesh, North Maharashtra, India. Physicochemical analysis of honey samples was conducted using established methods described by the Association of Official Analytical Chemists (AOAC 2012), and the protein content was determined using the Folin-Ciocalteau reagent method. Among the different sources of honey, significant differences were found across honey samples in terms of moisture content, pH, electrical conductivity, ash content, free acidity, protein, hydroxymethylfurfural (HMF), proline, and diastase activity. The honey samples from both bee species with different geographical and floral origins had varing ranges of moisture content (15.84%-23.16%), pH values (3.31-4.84), electrical conductivity (0.52-0.96 mS/cm), ash content (0.18%-0.51%), free acidity (26.83-40.18 meq/kg), protein content (1.45-3.05 g/kg), HMF levels (19.38-35.69 mg/kg), proline (223.49- 849.26 mg/kg), and diastase activity (9.46-21.57 DN). Notably, physicochemical parameters were significantly higher in A. dorsata honey than in A. c. indica honey. These variations highlight the influence of floral and geographical origin- on the physicochemical properties of honey. Furthermore, honey collected from forest sites was superior to that collected from agricultural and urban sites. All these values fall within the criteria set by international standards, highlighting the quality and compliance of honey samples. Principal component analysis (PCA) revealed a strong separation between the measured parameters, and was mostly dominated by moisture, pH, EC, ash, free acidity, protein, proline, and diastase.